ANALISIS KEPATUHAN PELAKSANAAN STANDARD OPERATIONAL PROCEDURE (SOP) PADA PEKERJA KELISTRIKAN DI PT. ANGKASA PURA I SEMARANG TAHUN 2016 - Kurniawan, Bina; Jayanti, Siswi (Jurnal Kesehatan Masyarakat (e-Journal), 2016)
One of the industrial accidents that often cause fatalities is electrical accident. Compliance to Standard Operational Procedure (SOP) has an important role in create electrical safe work. PT. Angkasa Pura I Semarang have electrical department that will supply of electricity for airport operational facilities for 24 hours with about 1100 kVA usage. This study aimed to analyze the compliance of electrical technician on SOP implementation in PT. Angkasa Pura I Semarang. This research is descriptive qualitative in-depth interviews and observation. The subject of this study amounted to 8 electrical technicians as key informants and 2 as triangulation informants (Safety Management System Section Head and Electricity Supervisor). The results showed electrical technician have had knowledge about SOP and also understand of their personal duties, electrical technician have positive attitude about SOP that every workers have to work based on SOP and also have positive perception about SOP from their assumption the importance of SOP, the availability of SOP and PPE are quite complete but especially for some PPE need to be upgrade more, supervisor has important role at work, to do assistance with their workers,Â  but only for some specific tasks. The conclusion of this study is the compliance of electrical technician on SOP implementation at daily work is good, otherwise the compliance on maintenance activities still need to be improved. It is because the educational background of all the workers is Electrical Vocational High school. Eventhough, for maintanance job, technician often careless to comply the SOP.Â  Companies need to increase supervision to discipline every workers behavior in order to always follow the work step in SOP for every kind of tasks and also provide the supporting facilities for example PPE.